1983
DOI: 10.1093/bja/55.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sensitivity of a and C Nerve Fibres to Long-Acting Amide Local Anaesthetics

Abstract: The differential sensitivities of A beta, A delta and C fibres of rat vagus nerve to bupivacaine, etidocaine and AL-381 were studied in vitro. In A beta fibres, at 35-37 degrees C, 50 mumole litre-1 of the drugs had similar effects on the action potential amplitude, while at greater concentrations (100 and 200 mumole litre-1) the greatest mean depression of amplitude was seen with etidocaine (n.s.). AL-381 had the most marked effect on the A delta potentials, and it appeared that it was about twice as potent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(32 citation statements)
references
References 9 publications
2
30
0
Order By: Relevance
“…In addition, in most institutions, a test dose of local anesthetic is used before the definitive dose is injected and the local anesthetics are used with opioids, thus making it difficult to choose the anesthetic concentration of a particular agent by the measured MLAC value alone. In the study by Gautier et al 1 2 the patients given bupivacaine 0.1% with sufentanil rated their analgesia to be unsatisfactory and this concentration of bupivacaine is higher than its recently reported 8 MLAC. On the contrary, our study evaluated the sensory and motor effects of local anesthetic infusions administered during the course of first stage in primiparous women and, therefore, more likely represents the clinical efficacy of the agents studied.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, in most institutions, a test dose of local anesthetic is used before the definitive dose is injected and the local anesthetics are used with opioids, thus making it difficult to choose the anesthetic concentration of a particular agent by the measured MLAC value alone. In the study by Gautier et al 1 2 the patients given bupivacaine 0.1% with sufentanil rated their analgesia to be unsatisfactory and this concentration of bupivacaine is higher than its recently reported 8 MLAC. On the contrary, our study evaluated the sensory and motor effects of local anesthetic infusions administered during the course of first stage in primiparous women and, therefore, more likely represents the clinical efficacy of the agents studied.…”
Section: Discussionmentioning
confidence: 90%
“…13 Several studies have found that sensory blockade is obtained with lower concentrations. 14,15 Lower concentrations of ropivacaine may also have a selective analgesic effect because clinically they block thin A␦ and C nerve fibers more readily than large A␤ fibers. 15 Although ropivacaine at low concentrations may be suitable for providing postoperative analgesia, as shown for outpatient hernia surgery performed under spinal anesthesia, 4 higher concentrations are required for effective surgical anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…In our study with amphibian myelinated nerve, flicker K + channels are more frequently found in thin nerve fibers ( < 5 Ixm) which in general conduct pain. Therefore, a specific blockade of these fibers may lead to a predominant block of pain, a so-called differential nerve block (Rosenberg and Heinonen, 1983;Raymond and Gissen, 1987). In fact, bupivacaine and ropivacaine in low concentrations are clinically used for this purpose.…”
Section: A New Mode Of Nerve Blockmentioning
confidence: 99%